The association between genetic variants in hMLH1 and hMSH2 and the development of sporadic colorectal cancer in the Danish population - Syvänen Ann-Christine; Olsen Anja; Tjønneland Anne; Koed Karen; Wiuf Carsten; Wikman Friedrik P; Madsen Bo E; Christensen Lise; Andersen Claus L; Ørntoft Torben F (BMC, 2008)
Abstract Background Mutations in the mismatch repair genes hMLH1 and hMSH2 predispose to hereditary non-polyposis colorectal cancer (HNPCC). Genetic screening of more than 350 Danish patients with colorectal cancer (CRC) has led to the identification of several new genetic variants (e.g. missense, silent and non-coding) in hMLH1 and hMSH2. The aim of the present study was to investigate the frequency of these variants in hMLH1 and hMSH2 in Danish patients with sporadic colorectal cancer and in the healthy background population. The purpose was to reveal if any of the common variants lead to increased susceptibility to colorectal cancer. Methods Associations between genetic variants in hMLH1 and hMSH2 and sporadic colorectal cancer were evaluated using a case-cohort design. The genotyping was performed on DNA isolated from blood from the 380 cases with sporadic colorectal cancer and a sub-cohort of 770 individuals. The DNA samples were analyzed using Single Base Extension (SBE) Tag-arrays. A Bonferroni corrected Fisher exact test was used to test for association between the genotypes of each variant and colorectal cancer. Linkage disequilibrium (LD) was investigated using HaploView (v3.31). Results Heterozygous and homozygous changes were detected in 13 of 35 analyzed variants. Two variants showed a borderline association with colorectal cancer, whereas the remaining variants demonstrated no association. Furthermore, the genomic regions covering hMLH1 and hMSH2 displayed high linkage disequilibrium in the Danish population. Twenty-two variants were neither detected in the cases with sporadic colorectal cancer nor in the sub-cohort. Some of these rare variants have been classified either as pathogenic mutations or as neutral variants in other populations and some are unclassified Danish variants. Conclusion None of the variants in hMLH1 and hMSH2 analyzed in the present study were highly associated with colorectal cancer in the Danish population. High linkage disequilibrium in the genomic regions covering hMLH1 and hMSH2, indicate that common genetic variants in the two genes in general are not involved in the development of sporadic colorectal cancer. Nevertheless, some of the rare unclassified variants in hMLH1 and hMSH2 might be involved in the development of colorectal cancer in the families where they were originally identified.